Geomechanical study of the Bi-stabilization of clay with sugarcane molasses and coconut fiber for sustainable construction - Boukaré Ouédraogo; Inoussa Tougri; Hassime Guengané; Kalifa Palm; Dieudonné Joseph Bathiebo (Materials Research Express)
This study examines the effectiveness of the bi-stabilization of clay soils using cane molasses and coconut fiber, focusing on improving the geotechnical and mechanical properties of clay. The performance of the two stabilizers, both individually and in combination for bistabilization, was assessed. The geotechnical properties were determined through sieve analysis, Proctor tests, and Atterberg limit methods, while the mechanical properties were measured using a hydraulic press. The results showed that cane molasses reduced plasticity, enhanced soil cohesion, and increased dry density with molasses content. The Atterberg limits (liquid limit, plastic limit, and consistency index) were maximized at a 4% molasses content, with respective increases of 9.28%, 44.80%, and 37.9% compared to clay without molasses (CB). Coconut fiber improved the flexural strength by 361.9% for CF1, whereas molasses improved the compressive strength by 12.24% compared to plain clay. Bi-stabilization allowed for a maximum improvement in flexural strength of 509.52% compared to CB, 49.42% compared to molasses-stabilized clay bricks (CSM), and 31.96% compared to clay composites with coconut fiber (CF). The compressive strength improved by 22.54% compared with CB, 9.21% compared with CSM8, and 14.94% compared with CF½. In summary, bi-stabilization with sugarcane molasses and coconut fiber provided enhanced performance compared with their individual use.